(untitled) (College of Basic Education Research Journal, 2026)
The importance of this research lies in developing a training program that enhances players’ physical and technical skills, this is achieved by increasing the exercise volume in training sessions to develop the physical and skill abilities of deaf and mute football players, based on the researcher’s experience in the training field, he observed variations in physical and skill levels during athletic activity. Therefore, the researcher decided to develop standardized competitive exercises within the training load to prepare the player to maintain the same level of performance and movement patterns. The research aimed to identify differences between the experimental and control groups in certain physical and skill variables for deaf and mute football players. The research population consisted of 16 players from the Nineveh Governorate football team for deaf and mute individuals with special needs, participating in the 2025 sports season. The sample was divided into an experimental group and a control group, each containing 8 players. The most important conclusion is that competitive exercises have a positive effect on certain physical and skill variables for deaf and mute football players, The researcher recommends emphasizing competitive exercises in the training of people with special needs